Changes in Arrangement of Chondrons in Radial Zone of Ageing Male Human Articular Cartilage - Shaista Ali,Samia Sarwar,Ifra Saeed (Journal of Rawalpindi Medical College, 2016)
Background: To study the variation in arrangement of chondrons in radial zone of male human articular cartilage. Methods: Forty samples of articular cartilage from male dead bodies ageing between 21 – 60 years were collected and divided into four groups. After tissue processing and cutting, H&E and special staining with Masson’s Trichrome was done and arrangement of chondrons was noted. Results: With advancing age the arrangements of chondrons in radial zone of group A, B and C was in short columns while in group D, the arrangement was disturbed. The chondrons were observed in pairs and clusters. Conclusion: In ageing articular cartilage the arrangements of chondrons in radial zone of articular cartilage is altered leading to osteoarthritis that makes it focus of intense study for preventive measures and treatment.